2008
DOI: 10.1007/s11365-008-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

Market entry of firms with different legal forms: an empirical test of the influence of institutional factors

Abstract: Drawing upon institutional theory we develop a conceptual model and investigate the determinants of market entry for worker cooperatives, publicly traded and limited-liability companies. Our results show that formal institutional conditions (i.e., mercantile legislation) influence the start-up choice of entrepreneurs regarding the legal form of their new venture. In addition, we take into account the influence of informal institutional conditions (i.e., local corporate culture) on the market entry rate of firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
0
28
0
4
Order By: Relevance
“…In other words, it seems appropriate to pose the question: are there differences in terms of cooperative essence according to different environments or contexts? In this regard, different studies have found that the creation of cooperatives may be promoted by an environment with informal and institutional factors favourable to cooperatives, such as a high-functioning cooperative culture, a high number of already existing cooperatives, and policies and subsidies related to cooperatives (Perotin 2006, Arando et al 2009. The reason that explains this is that this situation allows these firms to become widely recognized and embraced by society.…”
Section: Cooperative Essencementioning
confidence: 99%
“…In other words, it seems appropriate to pose the question: are there differences in terms of cooperative essence according to different environments or contexts? In this regard, different studies have found that the creation of cooperatives may be promoted by an environment with informal and institutional factors favourable to cooperatives, such as a high-functioning cooperative culture, a high number of already existing cooperatives, and policies and subsidies related to cooperatives (Perotin 2006, Arando et al 2009. The reason that explains this is that this situation allows these firms to become widely recognized and embraced by society.…”
Section: Cooperative Essencementioning
confidence: 99%
“…Creación de cooperativas y dimensión del sector cooperativo La literatura sostiene que la presencia y creación de cooperativas es marginal en relación con la de empresas capitalistas en la mayoría de sectores de actividad y países (Ben-ner, 1988) debido a diversos factores. En primer lugar, se señala que las cooperativas se crean fundamentalmente en etapas cortas caracterizadas por la recesión económica y el desempleo debido a su carácter anticíclico, desapareciendo en etapas de recuperación o crecimiento económico (Pérotin, 2006;Arando et al, 2009). Asimismo, se sugiere que la creación de cooperativas depende de la existencia de instituciones formales e informales en mayor medida que las empresas capitalistas.…”
Section: La Internacionalización Empresarial: Una Breve Contextualizaunclassified
“…As for the regulatory dimension of institutions, laws, regulations, and government policies constitute formal institutions that can enhance, support or inhibit entrepreneurship as they increase or reduce the risks for individuals starting a new firm, and facilitate entrepreneurs' efforts to acquire resources (Veciana and Urbano, 2008;Arando, Peña & Verheul, 2009). Our study was conducted in a single country and thus, our data did not allow us to test the effect of different national-level legal frameworks and institutions on immigrants' entrepreneurial projects.…”
Section: Environmental Factorsmentioning
confidence: 99%